The Unforeseen Digital Eye Strain of Children : A Review - Irawaty, Dian Kristiani; Oktaviani, Maya (Universitas Nahdlatul Ulama Surabaya, 2023)
People of all ages are using mobile devices more frequently, and more children are reportedly using digital media as well, which raises the risk of Digital Eye Strain (DES). There have been few studies on how often DES affects children particularly post-pandemic. The purpose of this study is to review published literature concerning DES, including its pathogenesis and therapy options. A literature search was performed based on PubMed, EMBASE and Scopus databases published from 2003 to 2023 using the broad search term “digital eye strain”, “ocular asthenopia secondary to digital gadgets”, “computer vision syndrome”, “eye strain post-computer or mobile use”, “visual weariness”, and “children